2019
DOI: 10.1111/nph.16311
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of land‐plant‐specific glycerol‐3‐phosphate acyltransferases is essential for cuticle formation and gametophore development in Physcomitrella patens

Abstract: Summary During the evolution of land plants from aquatic to terrestrial environments, their aerial surfaces were surrounded by cuticle composed of cutin and cuticular waxes to protect them from environmental stresses. Glycerol‐3‐phosphate acyltransferase (GPAT) harboring bifunctional sn‐2 acyltransferase/phosphatase activity produces 2‐monoacylglycerol, a precursor for cutin synthesis. Here, we report that bifunctional sn‐2 GPATs play roles in cuticle biosynthesis and gametophore development of Physcomitrell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 63 publications
0
25
0
Order By: Relevance
“…Penetration pores were detected on the surface of P. patens cell walls and in intercellular spaces that are colonized by infection hyphae that subsequently invaded leaf cells [27]. Cutinases may be involved in gametophore colonization since fungal penetration pegs penetrate the tissues directly through leaf cell walls [53], and protonema cells have no cuticle [76]. In addition, some B. cinerea cutinases show high homology to acetylxylanesterases [77], and could be involved in degradation of xylans in moss tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Penetration pores were detected on the surface of P. patens cell walls and in intercellular spaces that are colonized by infection hyphae that subsequently invaded leaf cells [27]. Cutinases may be involved in gametophore colonization since fungal penetration pegs penetrate the tissues directly through leaf cell walls [53], and protonema cells have no cuticle [76]. In addition, some B. cinerea cutinases show high homology to acetylxylanesterases [77], and could be involved in degradation of xylans in moss tissues.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently reported that K. nitens produces a considerable amount of fatty acids with simple linear carbon chain length from C16 to C18 that attach to cell wall components, when grown on solid medium (Kondo et al ., 2016). Intriguingly, the moss P. patens at the protonema stage produces a smooth hydrophobic layer of only fatty acids, with C16 as a major constituent, that resembles the secretions of K. nitens , while gametophores develop a cutin layer (Lee et al ., 2020). Our observations support the idea that fatty acids were already a well‐established component in the common ancestors of land plants, with the potential to form a more complex polyester matrix by interaction with other well‐known cutin constituents in land plants, including DCAs and HFAs.…”
Section: Discussionmentioning
confidence: 99%
“…To some extent, this genetic regulatory gene network contains likely orthologues of known genes involved in the cuticle biosynthesis pathway in vascular plants; however, many of the genes and their orthologues have not been functionally analysed in either vascular plants or early‐diverging land plants (Table S7). From this putative MIXTA‐regulated cuticle gene network, so far only GPAT (Lee et al ., 2020) and ABCG (Buda et al ., 2013) have been studied in P. patens , with the function of P. patens CUS only tested in vitro (Yeats et al ., 2014). However, we identified numerous additional putative homologues of cuticle synthesis genes, which lie within the MpSBG9 transcriptional network, but which are functionally uncharacterized.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we observed the ubiquitous expression of PpGPAT9 during the life cycle of P. patens life (Figure 2). Interestingly, we tried to generate P. patens gpat9 mutants by homologous recombination [35]; however, it was not successful under similar conditions in which knockout mutants of PpGPAT2 and PpGPAT4 involved in cutin synthesis were generated [55]. When PpGPAT9 is overexpressed in Arabidopsis, the total FAME levels increased in PpGPAT9 OX seeds, and alterations in the fatty acid composition of PpGPAT9 OX seeds and leaves were observed when compared with the wild type (Figure 6).…”
Section: Discussionmentioning
confidence: 99%